The school, one of the first formal places for the first immoral actions - Ventura Montes, Ulises (2023)
The first social representation, more official and protocol, that children have is addressed and set at school. It is there where they exercise their first formal functions, typical of their age, changing its natural role for a formal and more interactive one. In this way, the child children are renamed the student children. And it is in this representation and social dynamism where they face endless moral questions. What motivations direct children to commit acts against morality? This is the question that guides our line of research. Five factors are considered: little experience, fear and coercion, masculinity, the absence of pedagogical accompaniment, the level of the primary school grade.